Sectoral Analysis of Keban District Biogas Potential and Its Contribution to District Electricity Consumption - Özdemir, Gönül; Salman, Meriç Yılmaz (My University, 2025)
As a result of the rapid increase in the world's population, non-renewable natural resources have begun to deplete and country administrations are looking for solutions to provide cheap and safe energy supply. At this point, biogas production comes to the fore as an alternative energy source. This study was carried out to determine the biogas production potential of agricultural, animal and industrial wastes in Keban district of Elazığ province and to evaluate the possible contribution of this potential to the electricity consumption of the district. The monthly biogas production capacity and the corresponding amount of electrical energy were calculated on a sectoral basis, taking into account the types and number of animals belonging to the district, agricultural production data and the amount of waste from the aquaculture processing plant. According to the results, the monthly amount of biogas that can be obtained only from these wastes in Keban district is approximately 104.559 m³ and the corresponding electricity generation capacity is approximately 507.638 kWh. This value is considerably higher than the monthly electricity consumption of Keban Municipality, which varies periodically. Animal wastes in particular offer a stable production potential throughout the year, while agricultural and industrial wastes contribute to production with seasonal fluctuations. The study results show that biogas technology can provide significant benefits not only in terms of energy production, but also in terms of waste management, environmental sustainability and rural development. In this context, an integrated biogas plant to be established in Keban district is thought to contribute to energy independence and environmentally sensitive development by expanding the use of renewable energy at the local scale.
Keywords: Renewable energy; Biogas; Animal waste; Agricultural waste.